Meeting of the ENFSI Textile and Hair Group (Zurich, Switzerland) - T. V. Perfilova; E. M. Nesterina (Теория и практика судебной экспертизы, 2018)
The paper presents the outcomes of the 26th Meeting of the ENFSI Textile and Hair Expert Working Group and the Animal Hair Workshop held in Zurich (Switzerland) on June 11–15, 2018.